DINAMIKA KISAH “SI KENCUR” DALAM MEMPERBAIKI SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS RETRIBUSI PELAYANAN PASAR: SUATU KAJIAN DRAMATURGI - Andry Yunanto; Ali Djamhuri; Yeney Widya Prihatiningtias (Jurnal Akuntansi Aktual, 2017)
This study aims to explore the role of actors in a story in improving the accounting information system in cash revenue of market retribution. The dynamics of the story tell about the story of the main character, "Si Kencur", on his efforts to improve the accounting information systems and provide insight and an in-depth picture about various issues in the play of local government’s bureaucracy. The theatrical analogy and dramatic plot in dramaturgy method is used as the framework to construct a story, to analyze the dialogue, and to conduct studies. The implementation of accounting information systems of cash revenue depends on the alignment of interest, the role support from all actors, either they are in front of, behind, or at any other stages, better stage setting, usage of information technology properties, and usage of associative strategy.Keywords: Accounting information systems, market retribution, dramaturgy